My Life as a Work of Art. - Tylvich, Katya; Eastham, Ben (Londen : Laurence King Publishing, 2016)
Creed, Martin ; McGee, Barry ; Henrot, Camille ; Parreno, Philippe ; Huyghe, Pierre ; Wurm, Erwin ; Borremans, Michaël ; Crewdson, Gregory
boek